2018
DOI: 10.2147/ijn.s160828
|View full text |Cite
|
Sign up to set email alerts
|

Silica nanoparticle exposure during the neonatal period impairs hippocampal precursor proliferation and social behavior later in life

Abstract: IntroductionSilica nanoparticles (SiO2-NPs) are currently among the most widely used nanomaterials, but their potentially adverse effects on brain development remain unknown. The developing brain is extremely sensitive to NP neurotoxicity during the early postnatal period.Materials and methodsHerein, we investigated the effects of SiO2-NPs (doses of 10, 20, or 50 mg with a particle size of ~91 nm, equivalent to aerosol mass concentrations 55.56, 111.11, and 277.78 mg/m3, respectively) exposure from postnatal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
2
5
1
Order By: Relevance
“…It has been reported that direct exposure to SiO 2 -NPs via inhalation from PD1 to PD7 does not impair offspring's memory (Fu et al, 2018). In contrast, the present study showed that maternal exposure to these NPs during PD1 to PD21 impairs adulthood's cognitive performance.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…It has been reported that direct exposure to SiO 2 -NPs via inhalation from PD1 to PD7 does not impair offspring's memory (Fu et al, 2018). In contrast, the present study showed that maternal exposure to these NPs during PD1 to PD21 impairs adulthood's cognitive performance.…”
Section: Discussioncontrasting
confidence: 87%
“…Silicon dioxide nanoparticles (SiO 2 -NPs), also known as nanosilica, are extensively produced worldwide and used in many products such as ceramics, paints, consumer products, cosmetics, rubs, soups, coffee creamers and composites; and even as food additives (Mohammadipour et al, 2020;Li et al, 2020;Zhu et al, 2019). It is reported that more than 1.5 million tons of SiO 2 -NPs are produced annually, with a high rate of entry into the body (Fu et al, 2018;Mohammadipour and Abudayyak, 2021). Because of the ultra-small size, SiO 2 -NPs enter the body through inhalation, ingestion and dermal contact (Du et al, 2019;Hirai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The widespread use of SiO 2 NPs in consumer products has caused controversy and concern due to its known neuro-, teratogenic, and developmental toxicity. [21][22][23] Our previous study showed that nano-scale silica particles can induce more severe cytotoxicity and autophagy dysfunction than micro-scale silica particles in a size-dependent manner. 24 Kim et al observed that approximately 60 nm SiO 2 NPs affect cells differently than nanoparticles of other sizes due to enhanced uptake.…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous method (Fu et al., 2018 ), mice were anesthetized and transcardially perfused with saline followed by 4% paraformaldehyde (PFA). Subsequently, the brains were postfixed in 30% sucrose solution with 4% PFA.…”
Section: Methodsmentioning
confidence: 99%